Isolation and characterization of novel S-equol-producing bacteria from brines of stinky tofu, a traditional fermented soy food in Taiwan. (22nd July 2013) - Abiru, Yasuhiro; Ueno, Tomomi; Uchiyama, Shigeto
Abstract: Six strains capable of transforming daidzein to S -equol were isolated from the fermented brines of stinky tofu purchased in Taiwan. Daidzein was completely converted into S -equol within 24h of incubation in five strains. All the strains were gram-positive, rod-shaped, obligately anaerobic, non-motile, and non-spore-forming. In a phylogenetic analysis based on 16S rRNA gene sequences, the strains distributed into three groups in the family Coriobacteriaceae . SNR40-432 (Group I) showed 98.6% 16S rRNA gene similarity and 48–49% DNA-DNA relatedness with Paraeggerthella hongkongensis HKU10 T, suggesting the possibility that SNR40-432 represents a new species in the genus Paraeggerthella . SNR48-44 (Group II) and SNR44-10, SNR45-571, SNR46-41, SNR48-350 (Group III) showed a maximum of 92.2 and 92.1% 16S rRNA gene similarities with Eggerthella sinensis HKU14 T and Eggerthella lenta JCM9979 T, respectively, which denotes that each group may represent a novel genus and species in the family Coriobacteriaceae . This is the first report isolating equol-producing bacteria from food.